The Role Of Website Design For Syrian Government Universities In Measurement The Quality Of Educational Services Case Study Of Tishreen University Website) ) - السكري, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aims to study the extent of the impact of website design for Syrian government universities (method of use, content, interactivity, attractiveness, service value) on evaluating the quality of educational services provided (reliability, responsiveness, security and reliability). To achieve this goal, a case study was conducted that included the Tishreen University website. The current study relied on the descriptive analytical approach. An electronic questionnaire was designed for the purpose of collecting primary data and was distributed to a purposive sample that included (300) male and female students from various colleges who had previously used the Tishreen University website. The collected data were then analyzed and hypotheses tested using SPSS.25. The study reached a set of results, the most important of which are: the existence of a statistically significant relationship between the design dimensions of the Tishreen University website and the quality of educational services provided by this website; There was a significant positive impact of using the university’s website on the security and reliability of the educational services it provides, and the interactivity of the website had a striking impact on the response of the students who used it, while the content of the website was the design criteria that had the least impact on the quality of the educational services provided, through its weak effect in the reliability of those services.